Assessing the efficacy: mid-term clinical and radiological outcomes of the comprehensive short stem system in reverse shoulder arthroplasty - Navas, Luis; Schmidt, Sebastian; Vogel, Carolina; Ulmar, Benjamin; Zimmerer, Alexander; Gühring, Thorsten (Journal of shoulder and elbow surgery, 2025)
Background - For degenerative shoulder disease, reverse shoulder arthroplasty (RSA) has proven successful; however, problems such as scapular notching and instability still exist. These difficulties are intended to be addressed by recently improved prosthesis designs with reduced neck-shaft angles (NSA). Still, there are issues with complications, particularly with the humerus. In an effort to avoid these problems and maintain bone stock, a recently designed straight-short-stem humeral component was used; however, yet its clinical and radiological outcomes in RSA remain largely unexplored. - Material and methods - Using a 55 mm straight short stem (Comprehensive Reverse Shoulder System; Zimmer Biomet), a retrospective analysis of 93 patients undergoing primary RSA was carried out. Clinical assessments, including scores and range of motion, were conducted both before and after surgery. Complications, bone adaptation, and stem alignment were all evaluated radiographically. Significant correlations between postoperative shoulder movements and function were linked with angles of prosthesis lateralization and distalization. - Results - Patients demonstrated significant improvements in clinical scores at 35-month follow-up on average: Constant-Murley (76.4 ± 13.4), American Shoulder and Elbow Surgeons (84.8 ± 16.5), Disabilities of Arm, Shoulder, the Hand (17.1 ± 15.8), and University of California and Los Angeles (7.1 ± 1.5). Radiographic assessments showed no stem loosening and stable implant attachment. There was no scapular notching, and there were noticeable improvements in shoulder range of motion and function. - Discussion and Conclusion - This study validates the efficacy of a straight short stem for acceptable clinical outcomes and implant stability in RSA. Notably, it demonstrates specific angle ranges crucial for optimal postsurgical shoulder function. The findings suggest this stem design presents potential benefits in RSA, highlighting its safety and effectiveness while providing insights for future clinical strategies. The study contributes valuable data toward understanding and enhancing patient outcomes in shoulder arthroplasty procedures.